Pressure Optimized PowEred Respirator (PROPER): A miniaturized wearable cleanroom and biosafety system for aerially transmitted viral infections such as COVID-19. (October 2020) - Nazarious, Miracle Israel; Mathanlal, Thasshwin; Zorzano, Maria-Paz; Martin-Torres, Javier
Abstract: The supply of Personal Protective Equipment (PPE) in hospitals to keep the Health Care Professionals (HCP) safe taking care of patients may be limited, especially during the outbreak of a new disease. In particular, the face and body protective equipment is critical to prevent the wearer from exposure to pathogenic biological airborne particulates. This situation has been now observed worldwide during the onset of the COVID-19 pandemic. As concern over shortages of PPE at hospitals grows, we share with the public and makers' community the Pressure Optimized PowEred Respirator (PROPER) equipment, made out of COTS components. It is functionally equivalent to a Powered Air Purifying Respirator (PAPR). PROPER, a hood-based system which uses open source and easily accessible components is low-cost, relatively passive in terms of energy consumption and mechanisms, and easy and fast to 3D print, build and assemble. We have adapted our experience on building clean room environments and qualifying the bioburden of space instruments to this solution, which is in essence a miniaturized, personal, wearable cleanroom. PROPER would be able to offer better protection than an N95 respirator mask, mainly because it is insensitive to seal fit and it shields the eyes as well. The PROPER SMS fabric is designed for single-use and not intended for reuse, as they may start to tear and fail but the rest of the parts can be disinfected and reused. We provide a set of guidelines to build a low-cost 3D printed solution for an effective PAPR system and describe the procedures to validate it to comply with the biosafety level 3 requirements. We have validated the prototype of PROPER unit for air flow, ISO class cleanliness level, oxygen and carbon-dioxide gas concentrations during exhalation, and present here these results for illustration. We demonstrate that the area inside the hood is more than 200 times cleaner than the external ambient without the operator and more than 175 times with the operator and in an aerosol exposed environment. We also include the procedure to clean and disinfect the equipment for reuse. PROPER may be a useful addition to provide protection to HCPs against the SARS-CoV-2 virus or other potential future viral diseases that are transmitted aerially.